Please urgent help with 3 and 4!!!!
![Please urgent help with 3 and 4 class=](https://us-static.z-dn.net/files/d65/2f76ae7f254ae5ed06e3569ef8ba9726.png)
Answer:
3) option C
Step-by-step explanation:
we have from the statement:
f(x)=[tex]\frac{\sqrt{x+3}}{x}[/tex]
g(x)= [tex]\frac{\sqrt{x+3}}{2x}[/tex]
so we have:
(f.g)(x)=[tex]\frac{\sqrt{x+3}}{x}[/tex] * [tex]\frac{\sqrt{x+3}}{2x}[/tex]
(f.g)(x)= [tex]\frac{(\sqrt{x+3})^{2} }{x*2x}[/tex]
(f.g)(x)=[tex]\frac{x+3}{2x^{2}}[/tex]
the answer is option C